Comparative Severity Assessment of Genetic, Stress-Based, and Pharmacological Mouse Models of Depression - Mallien, Anne Stephanie; Pfeiffer, Natascha; Brandwein, Christiane; Inta, Dragos; Sprengel, Rolf; Palme, Rupert; Talbot, Steven R.; Gass, Peter (Frontiers in Behavioral Neuroscience, 2022)
The use of animals in neurosciences is pivotal to gaining insights into complex functions and dysfunctions of behavior. For example, various forms of physical and/or psychological stress are inherent to various animal models for psychiatric disorders, e.g., depression. Regarding animal welfare, it would be mandatory to use models that inflict the least amount of stress necessary to address the underlying scientific question. This study compared the severity of different approaches to induce depression in mice: mutagenesis in GluA1 knockout, immobilization stress, and stress-induction via stress hormone treatment. While genetic alterations potentially represent a lifelong burden, the temporary intervention only affects the animals for a limited time. Therefore, we used home cage-based behavioral and physiological parameters, including nest building, burrowing, body weight, and fecal corticosterone metabolites, to determine the well-being of male and female mice. In addition, we performed an evidence-based estimate of severity using a composite score for relative severity assessment (RELSA) with this data. We found that even though restraint stress and supplementation of corticosterone in the diet both aimed at depression-related precipitating stress effects, the latter affected the well-being much stronger, especially in females. Restraint leads to less noticeable well-being impairments but causes depression-associated anhedonic behavior. Mice of both sexes recovered well from the stress treatment. GluA1 KO and their littermates showed diminished well-being, comparable to the immobilization experiments. However, since this is a lifelong condition, this burden is not reversible and potentially accumulative. In line with the 3Rs (Replacement, Reduction and Refinement), the process of choosing the most suitable model should ideally include an evidence-based severity assessment to be able to opt for the least severe alternative, which still induces the desired effect. Promoting refinement, in our study, this would be the restraint stress.